The statistical analysis of truncated and censored data under serial dependence - Strzalkowska-Kominiak, Ewa; Justus Liebig University Giessen (My University, 2008)
The subject of this work is estimation of two dimensional distribution function resp. integral w.r.t. such distribution function and the statistical analysis of this estimator in case when the data are incomplete. The variables of interest are lifetimes, where the first one is at risk of being truncated and the second can be censored. Additionally, the variables may be dependent. For example in the analysis of AIDS one often encounters data which are observed sequentially over time. In such a case the first variable can be the time elapsed between infection and seroconversion and the second may be the time between seroconversion and AIDS. A big part of the work deals with the Lynden-Bell estimator for truncated data and its proparties.

In der Arbeit handelt es sich um Schätzung und statistische Analyse des Schätzers einer zweidimensionalen Verteilungsfunktion bzw. eines Integrals bezüglich dieser Verteilungsfunktion anhand von unvollständigen Daten. Die Variablen von Interesse sind zwei nacheinander folgende Zeitintervalle (Lebensdauer), wobei der erste trunkiert und der zweite zensiert sein kann und die abhängig sein können. Der Modell findet Anwendung z.B. in medizinischen Studien über HIV. Dort ist die erste Variable, die Zeitspanne zwischen Infektion und Serokonversion und die zweite der Zeit zwischen Serokonversion und Diagnostizierung von AIDS. Ein Großteil der Arbeit beschäftigt sich allein mit Lynden-Bell Schätzer für Trunkierte Daten und dessen Eigenschaften.
Statistische Analyse von trunkierten und zensierten Daten bei Abhängigkeit
Keywords: Survival Analysis; Trunkierung; Zensierung; Survival Analysis; truncation; censorship; ddc:510